Pattern of Dermatological Diseases in the Patients of Army Hospital, Kathmandu - Jha, Sagar Mani; Rajbhandari, Sudarsan Lal; Shakya, Nabinbhakta; Pokharel, Arbind; Jha, Beena (Medical Journal of Shree Birendra Hospital, 2010)
Introduction: Human Skin is the largest organ of the body and may mirror the presence of benign/malignant systemic diseases in different ways. The pattern of Skin diseases vary in different parts ofNepal due to differences in socioeconomic and geographic factors. This retrospective study, pattern ofskin disease in Army Hospital likely reflects the pattern of disease in the Kathmandu Valley.Aim: To study, assess and compare the different patterns of skin disease in the patients attending theoutpatient department in the year 2007 and 2008 in the Army Hospital.Methods: This was a retrospective study and all the new cases which were diagnosed in the Department ofDermatology in the years 2007 and 2008 were included. The diseases were classified as Papulosquamous,Vesicobullous, Connectivetissue disorders, Skin and Soft tissue tumours, Infective, Eczema, SexuallyTransmitted Disease (STI), Leprosy and those skin diseases which were not coming under this formatwere classified as others.Result: The total number of cases recorded in the Department of Dermatology were 16828 in the year2007 and 18643 in 2008. It was found that the infective group of disorders were the largest group ofdisease, in the year 2007 a total of 6135 (36.4%) and in 2008 a total of 7883 (42.2%) had suffered from thisgroup of disorders. And the incidence of infective disorder was also statistically significant when both theyears were compared p-Value:0.00, OR:1.16, CI:1.11-1.21. Similarly other large groups were Eczema,papulosqumous and sexually tranmitted disease.Conclusion: It was found that the disease pattern in this study was lead by infective disease followed byeczema, papulosquamous disease and sexually transmitted disease.Key words: Eczema; Papulosquamous; VesicobullousDOI:  10.3126/mjsbh.v9i1.3484Medical Journal of Shree Birendra Hospital Vol.9(1) 2010 14-16